Nanofiber Semiconductor Experiment with Distance Variation Electrospinning Method to Improve DSSC Performance - Widhiyanuriyawan, Denny; Arifin, Zainal; Hadi, Syamsul; Fadli, Muhammad Rijalul (Universitas Sebelas Maret, 2022)
Dye-Sensitized Solar Cell (DSSC) is a solar cell that uses dyes to transfer sunlight to electrical energy. DSSC construction uses a layered system (sandwich) that consists of a working electrode and an opposing electrode, both of which are placed on conducting glass and electrolytes to allow electron cycling. DSSC has a high price, so increasing efficiency is needed to use these solar cells more widely. This research aims to determine the effect of the distance between the tip and the rotating collector to increase the efficiency of the Dye-Sensitized Solar Cell (DSSC) and examine its impact on the morphology of the ZnO nanofiber. This experiment is carried out by varying the distance between the tip to the rotating collector, 4 cm, 6 cm, and 8 cm. This research indicates that at a distance of 8 cm, it produces a small, uniform, and stable ZnO nanofiber structure with Voc, Jsc, FF, and DSSC efficiency values of 0.559 V, 9.809 mA/cm2, 43.3%, and 2.3%. In addition, at a distance of 8 cm, it also produces the highest DSSC electrical efficiency from the other distances due to the absorbance of the dye and high electron excitation.